Does glyceryl trinitrate cause central sympatholytic effects? Insights from a case of baroreflex failure. Issue 1 (14th January 2020) - Tan, Sarah; Xie, Lin; Anderson, Robert; Hammond, Andrew; Fong, Angelina Y.; Lim, Seok; Allen, Andrew M.; Harrap, Stephen B.
Abstract: Whether part of the blood pressure lowering effects of glyceryl trinitrate (GTN) is the result of centrally mediated reduction in sympathetic activity is debated. In humans, baroreflex activity potentially obscures the central sympatholytic effects of GTN. We examined this in a routine clinical tilt test in a patient with baroreflex failure secondary to previous neck radiotherapy. With reduced baroreflex function we observed an exaggerated fall in blood pressure and reduced sympathetic activity with GTN, supporting a peripheral vasodilation and central sympatholytic effect.